Analisis Respon Siswa terhadap Penggunaan Google Sites sebagai Media Pembelajaran Geografi di SMA Negeri 1 Kabila - Muhammad Rifqih R. Pango; M. Iqbal Liayong Pratama; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
The development of information and communication technology has encouraged the use of digital learning media to improve the quality of the learning process in schools. One such media is Google Sites, a website-based platform that allows for interactive presentation of learning materials through the integration of text, images, videos, and various other learning resources. This study aims to analyze student responses to the use of Google Sites as a Geography learning medium at SMA Negeri 1 Kabila. The study used a quantitative descriptive approach with 20 students of grades X-11 as research subjects. Data were collected through a Likert scale questionnaire covering five assessment aspects, namely appearance and accessibility, learning engagement and motivation, understanding of material and learning outcomes, ease of interaction and communication, and advantages and disadvantages of learning media. Data analysis was carried out using a percentage technique to measure the level of student responses to the use of Google Sites. The results showed that 80% of students stated that they strongly agreed, 15% agreed, and 5% disagreed with the use of Google Sites in Geography learning. These findings indicate that Google Sites received a very positive response because it was able to increase learning motivation, facilitate access to materials, support conceptual understanding, and create more interactive and flexible learning. Thus, Google Sites can be used as an alternative effective website-based learning media to support Geography learning and improve the quality of learning in the digital era.Analisis Respon Siswa terhadap Penggunaan Google Sites sebagai Media Pembelajaran Geografi di SMA Negeri 1 Kabila